Our government, people and values a proposed learning in social studies II - Sevilla, Aleli Villena 1951- (1979)
This study aimed to propose a model learning unit for Social Studies II - Philippine History and Government revolving around the concepts of government, people, and values. The current trends in the New Social Studies was discussed highlighting the rationale, objectives, content, process, evaluation, and the role of the teacher in the new learning situation. Objectives and processes that develop the needed understanding, skills, and values in the teaching of the "new" social studies served as the guide in preparing the learning unit. The conceptual theme and subconcepts for each chapter have been treated and covered adequately in the development of the unit. Learning experiences were also drawn from the different disciplines of the social sciences. It also provided materials and sequential activities for each reading that would guide both teachers and pupils in using facts in the development of concepts and generalizations.